(untitled) (Comprehensive Journal of Science, 2026)
This study aims to measure the impact of transactional leadership, with its three dimensions—contingent rewards, active management by exception, and passive management by exception—on the level of organizational trust among employees at the Khoms Telecommunications Office. The researcher employed a questionnaire consisting of 22 items, including a tool to measure transactional leadership (15 statements) and another to measure organizational trust (7 items). The questionnaire was distributed to all members of the population (40 employees), and all forms were retrieved with a 100% response rate. Data were analyzed using means, standard deviations, Pearson’s correlation coefficient, and multiple regression analysis to identify the nature of the relationship between transactional leadership and organizational trust. The findings revealed a significant effect of transactional leadership, across all three dimensions, on organizational trust among employees of the Khoms Telecommunications Office. Results indicated that contingent rewards, active management by exception, and passive management by exception are all statistically correlated with organizational trust, confirming that the relationship between these variables is not random but meaningful, thereby highlighting the importance of transactional leadership in fostering trust within organizations.